Language policy as reflected in the linguistic landscape in George Town, Penang / Beh Yn Jiou - Beh , Yn Jiou (2017)
This is a sociolinguistic study on language policy and language planning in Malaysia. The Linguistic Landscape (LL) approach will be adopted as a framework to investigate the language use on signs in the public space of George Town, Penang, specifically on Penang Road. By reviewing the language choice on signs in public space, it aims to evaluate how language policy of Malaysia is reflected in reality. Both qualitative and quantitative methods will be used in the study. For the quantitative method, photos of signs in public space has been taken using a digital camera. The collected data has been processed by software File Maker. Interviews has been carried out to complement the quantitative method. The findings of the study show that Penang Road is highly multilingual with numerous languages visible in the linguistic landscape. Although Malay language is advocated as the national language in the national language policy, and the language is a must in signage policies, the actual practice shows the contrary. It has been found that there is inconsistency between the prescribed language policy and the actual languages used on the billboard advertisements. It is hoped that the result of this study will enhance the understanding of the linguistic landscape of the multilingual and multiethnic society of Malaysia and have implications on the implementation of national language policy.